Improvements in potentiometric determinations of the CO2 oceanic system using seawater sub-standards and CO2 reference materials - Ríos, Aida F.; Pérez, Fiz F. (Universidad Autónoma de Baja California, 1999)
19 páginas, 12 figuras, 1 tabla [EN] During the Cither 3 cruise along WOCE section A14, where 107 full-water column stations were surveyed, pH and alkalinity were measured potentiometrically. Corrections carried out on the raw data set have allowed us to improve the data quality. The correction procedure was focused on monitoring: (i) calibrations, (ii) liquid junction potential and (iii) seawater sub-standards; CO2 reference material (CRM) has been used to check this procedure. Accuracy of pH15 measurements (NBS scale) and alkalinity was 0.004 and 1.4 μmol.kg–1, respectively. Certified total inorganic carbon on CRM, batch 24, is 1987.55 μmol.kg.–1. A value of 1987.8 ± 2.2 μmol.kg–1 was obtained following the correction procedure. This improvement was independently verified by means of the covariances between nitrate and pH, and between silicate and normalized alkalinity in North Atlantic Deep Water. [ES] Durante el crucero Cither 3, a lo largo de la sección WOCE A14, se midieron potenciométricamente pH y alcalinidad, en las 107 estaciones examinadas en toda la columna de agua. Las correcciones llevadas a cabo a los datos brutos permitió mejorar la calidad de los mismos. El procedimiento seguido en la corrección estuvo enfocado en controlar: (i) las calibraciones, (ii) el potencial de unión líquida y (iii) el agua de mar subestándar. El material de referencia de CO2 (CRM) ha sido utilizado para comprobar este procedimiento. La exactitud de las medidas de pH15 (escala NBS) y alcalinidad fue 0.004 y 1.4 μmol.kg–1, respectivamente. El carbono inorgánico total certificado para el CRM, lote 24, es 1987.55 μmol.kg–1. Un valor de 1987.8 ± 2.2 μmol.kg–1 se obtuvo siguiendo el procedimiento de corrección. Esta mejora fue independientemente verificada por medio de covarianzas entre nitrato y pH, y entre silicato y alcalinidad normalizada en Agua Profunda Noratlántica This work was supported by CICYT (grant number ANT94-1168-E) and IFREMER (University contract number 94-1430-087) Peer reviewed